Changes in Monoaminergic Neurotransmission in an Animal Model of Osteoarthritis: The Role of Endocannabinoid Signaling - Mlost, Jakub; Wąsik, Agnieszka; Michaluk, Jerzy Tadeusz; Antkiewicz-Michaluk, Lucyna; Starowicz, Katarzyna (Frontiers in Molecular Neuroscience, 2018)
Chronic pain is a main symptom of osteoarthritis (OA). Moreover, a high percentage of OA patients suffer from mental health problems. The endocannabinoid (EC) system has attracted attention as an emerging drug target for pain treatment together with its activity on the mesolimbic reward system. Understanding the circuits that govern the reward of pain relief is crucial for the search for effective analgesics. Therefore, we investigated the role of the EC system on dopamine (DA) and noradrenaline (NA) in an animal model of OA-related chronic pain. OA rats exhibited significant decreases in DA metabolism in the nucleus accumbens (NAc), striatum (STR) and hippocampus (HC). NA metabolism was also significantly decreased by chronic pain in OA rats; however, this disruption was limited to the frontal cortex (FCx) and hippocampus (HC). URB597 (an inhibitor of endocannabinoid metabolism) treatment completely reversed the decreased dopamine metabolism, especially in the brain reward system and the HC. Furthermore, administration of URB597 normalized the impairment of NA activity in the HC but potentiated the decreased NA levels in the FCx. Our results demonstrated that chronic pain in OA rats was reflected by the inhibition of mesolimbic and mesocortical dopaminergic transmission, and may indicate the pro-pain role of NA in the FCx. The data provide understanding about changes in neurotransmission in chronic pain states and may explain the clinical improvement in perceived life quality following cannabinoid treatment. Additional mechanistic studies in preclinical models examining the intersection between chronic pain and reward circuits may offer new approaches for improving pain therapy.